Brotherband : The Outcasts - Book 1 - Flanagan, John (John Anthony) (New York : Philomel Books, 2011)
Hal, who does not fit into Skandian society, ends up in a brotherband, a group of boys learning the skills that they need to become warriors, with other outcasts, and they compete with other brotherbands in a series of challenges.
"Companion to the ... Ranger's apprentice."
Originally published: North Sydney, N.S.W. : Random House Australia, 2011.
Keywords: Friendship -- Fiction; Fiction; Fiction